Praktik Pedagogik Pembelajaran Mendalam dalam Pengajaran Bahasa Inggris di Sekolah Dasar - Ana Utami Fatoni; Sakilah Bewafa; Sri Nurul Salimin Afamery (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study positions deep learning as a pedagogical orientation for English in elementary schools, where the subject is compulsory and aligned with A1 targets of the CEFR. The focus is on building students’ vocabulary, speaking, and reading competencies through authentic tasks. The research examines four complementary approaches—Inquiry-Based Learning (IBL), Project-Based Learning (PjBL), Problem-Based Learning (PBL), and Collaborative Learning (CL)—and analyzes how each is enacted to support competency attainment. For each approach, the analysis considers learning objectives, task design, scaffolding strategies, interaction patterns, and assessment practices, with attention to how activities elicit A1-level language use. The study maps IBL to exploration of simple questions and word discovery, PjBL to creation of multimodal products integrating basic vocabulary and short utterances, PBL to problem scenarios requiring functional phrases, and CL to structured pair or group exchanges rehearsing reading aloud and turn-taking. Findings highlight design principles advancing early proficiency: input models, segmented practice, repeated exposure to high-frequency items, visual supports, and feedback focused on intelligibility. The paper proposes an integrative framework sequencing the four approaches across units, ensuring progression from guided exploration to independent performance. Implications are offered for lesson planning, teacher support, classroom material design, and formative assessment aligned with CEFR A1 outcomes.